2014
DOI: 10.1080/1461670x.2014.891857
|View full text |Cite
|
Sign up to set email alerts
|

Shares, Pins, and Tweets

Abstract: This paper compares the volume of news articles per section in newspapers and social media platforms. To this end, two weeks of news articles were retrieved by querying the public Application Programming Interfaces (APIs) of The New York Times and The Guardian and the diffusion of each article on social media platforms Twitter, Facebook, Google+, Delicious, Pinterest, and StumbleUpon, was tracked. The results show significant differences in the topics emphasized by newspaper editors and social media users. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 25 publications
0
29
0
9
Order By: Relevance
“…According to more recent studies, hard news stories tend to attract more attention than soft news ones in social media. A recent content analysis of the stories published in The Guardian's and The New York Times' social media pages showed that users engaged more with hard news stories than soft news even though the editors of these newspapers prioritized soft news content in social media (Bastos, 2015). Another study suggests that apart from receiving more comments in general, hard news also attracts more uncivil comments than soft news stories (apart from sports) (Coe, Kenski, & Rains, 2014).…”
Section: Hard News Soft News and Participationmentioning
confidence: 99%
“…According to more recent studies, hard news stories tend to attract more attention than soft news ones in social media. A recent content analysis of the stories published in The Guardian's and The New York Times' social media pages showed that users engaged more with hard news stories than soft news even though the editors of these newspapers prioritized soft news content in social media (Bastos, 2015). Another study suggests that apart from receiving more comments in general, hard news also attracts more uncivil comments than soft news stories (apart from sports) (Coe, Kenski, & Rains, 2014).…”
Section: Hard News Soft News and Participationmentioning
confidence: 99%
“…The fact that they are engineered to attract human emotions such as curiosity, hopes and fears as well as the optimization for social media facilitate the creation of content that drives engagement (Moses, 2014). In the same vein, feedback to article may depend on the appeal of the article (Bastos, 2014). A recent study by psychologists found that misleading headlines have a significant effect on readers' memory for news articles as well as their inferential reasoning (Ecker et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In another relevant study, informativeness was the strongest motivation regarding news sharing intention in social media, followed by socializing and status seeking (Lee, Ma, & Goh, 2011). Finally, social media users tend to favor hard news (opinion pieces, national and world news) over soft and general news (Bastos, 2014). To sum up, the new features provided by social media have the potential to change the nature of news sharing.…”
Section: Social Network and Information Sharing Motivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies have used quantitative methodologies and have focused on analyzing the type of news shared, as well as the social network used (Bastos, 2015). According to these studies, Facebook is more widely used to share material relating to entertainment, while Twitter is more closely linked to current affairs or hard news (Newman, 2011), and the users sharing material on Twitter are older than those sharing on Facebook (Newman;Levy, 2014).…”
Section: Introductionmentioning
confidence: 99%